Sustaining the well-being of family with working spouse: income sharing dimension / Fadhilah Adibah Ismail … [et al.] - Ismail, Fadhilah Adibah; Ab Manan, Siti Khadijah; Saidon, Rafeah; Sahari, Noorul Huda; Abd Aziz, Azhar; Jaapar, Nurzahidah (Academy of Contemporary Islamic Studies (ACIS), 2018)
Muslim families traditionally maintain the conservative role of mothers being at home to manage family matters including bringing up children and juggling up with house-chores. Nevertheless, it is now becoming phenomenon in Malaysia where wives work to assist their husbands financially. The main aim is to ease the financial burden of the family as the present cost of living is increasing and financially demanding. This phenomenon however, may affect the family wellbeing as the time spent by the wives at home is limited hence disturbing the normal routine of managing the household chores, educating the children and taking care of them. The children might be somewhat neglected while the household chores might be out of control. In fact, there were also cases where financially independent working wives resulted in the husband being negligent in spending for the family needs, causing the wives to take care of almost all of the expenses of the household. This has led to many cases of marital problem. Hence, this study aims to examine the well-being of families where the wives are mostly working. There are several dimensions of maintaining family well-being such as the income and spending aspects of working spouses, time spent with family, conflicts encountered, health of family members and balance of savings at month end. This study only focused on the income and spending aspects of working spouses. The study adopts quantitative method through survey. Finding of the study implied that sharing of income by the wives would contribute to the sustainability and happiness of a marriage. This study is expected to add to the new frontier of knowledge in understanding the importance of income sharing between working husband and wife including the challenges they might encounter.